HUKUM ADAT DALAM PEMBENTUKAN HUKUM ISLAM DI INDONESIA (Konsep dan Implementasinya) - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
This article discusses customary law in the formation of Islamic law in Indonesia. The results of the discussion obtained an understanding that customary law is original Indonesian law which is not written / contained in the statutory form of the Republic of Indonesia and here and there contain religious elements. Meanwhile, Islamic law is a regulation that is taken from Allah's revelation and formulated in four thought products, namely: Fiqh, Ulama Fatwa, Court Decisions (Jurisprudence) and Laws (Qanun) which are guided and enforced for Muslims in Indonesia. The implementation of customary law in the formation of Islamic law in Indonesia can be seen in the process of fostering Islamic law which enforces the rule of al-adātul al-muhakkamāt. This means that customs that are not contrary to syara 'can be adopted within the framework of fiqîh that is enforced in Indonesia. The familiar relationship between customary law and Islamic law can be interpreted from expressions in several regions. For example: (Aceh)